Osteology of deinonychus antirrhopus, an unusual theropod from the lower cretaceous of Montana - Ostrom, John H. (Peabody Museum of Natural History, Yale University, 2019)
"Two original scientific descriptions by John H. Ostrom of the fossil type specimen of the Early Cretaceous biped theropod dinosaur Deinonychus antirrhopus presenting its avian-like skeletal anatomy, adaptations, habits, and affinities, research on functional morphology and the evolution of birds that led to the 'dinosaur renaissance' at the end of the 20th century"--